Getting Your Paper Published Fast: Medwave Stats Before and After Introducing Author Fees [Su Trabajo Publicado Rápidamente: Las Estadísticas de Medwave Antes y Después de Introducir la Política de Cobro a Autores] - Bachelet-Norelli, V (Medwave Estudios Ltda, 2019)
[No abstract available]